Políticas de mobilidade na cidade de Fortaleza: uma avaliação do ambiente de circulação de pedestres no Bairro Rodolfo Teófilo na Gestão Municipal 2013-2020 - Mota, Andre Silva Gomes (2022)
Federal Law 12,587/2012 instituted the National Urban Mobility Policy and required Brazilian municipalities with more than twenty thousand inhabitants to prepare Urban Mobility Plans, in accordance with the principles, guidelines and objectives of the Law. Among the guidelines is the priority of non-motorized transport modes over motorized ones. The present research sought to investigate the laws, plans and actions of urban mobility during the municipal administration 2013-2020 in Fortaleza CE, in order to observe the coherence of the public policy of valuing mobility on foot in the city with the guideline of prioritizing modes not vehicles, having as a case study an analysis of the quality of pedestrian space in the Rodolfo Teófilo neighborhood. Inconsistencies are revealed in the influence of the real estate and tourism market in the choice of mobility actions that benefited areas already equipped with infrastructure, in works incompatible with walking mobility, such as the construction of tunnels, viaducts, binary and in the legislation that continues to maintain. the property owner as primarily responsible for the maintenance, construction and repair of the sidewalk. The methodology used in this dissertation is based on the triangulation of methods (MINAYO et. al., 2005) and bibliographic research about the importance of mobility on foot in the current context, in the collection of data in laws, plans and documents, in the realization of questionnaires with pedestrians and in field observation. The research is inspired by the theoretical-methodological conception of evaluation by Lejano (2012), Rodrigues (2008) and Silva (2008) in the search for existing contradictions in the policy. Furthermore, it is supported by leading authors in urban planning such as Gehl (2013), Jacobs (2009), Speck (2016), Malatesta (2008; 2018), Vasconcellos (2000; 2016), Boareto (2003; 2021), but also in authors who research on the theme of urban mobility in the city of Fortaleza, such as Santiago (2013), Santiago and Morano (2019), Morano (2018), Cavalcante (2017) and Cavalcante, Morano and Santiago (2018).